Hemolysis detection for ethanol measurement in whole blood samples before centrifugation: HemCheck device evaluation - Zengi, Oguzhan; Boz, Meltem; Yesil, Beyazit Semih; Gumus, Alper (Journal of Medical Biochemistry, 2023)
Introduction As previously reported, hemolysis interference affects ethanol measurements as well. Ethanol is the most commonly abused substance worldwide. When sample re-collection is ordered to eliminate hemolysis effects for ethanol testing, this can have unfavorable consequences for these patients. Rapid detection of hemolyzed specimens would alleviate some issues associated with forensic samples. HemCheck™ is a novel POCT device that qualitatively detects free-hemoglobin levels on the specimen shortly after drawing the sample. Materials and methods The system consists of two components. One is a cartridge with a needle that is used to transfer a small volume of whole blood from a vacuum tube to vertical and lateral flow filtration. The second component is a reader. Consumable cartridges are inserted into the reader without the syringe or blood collection tube being removed. A red indicator led illuminates, indicating that the sample has been hemolyzed. We calculated C5-C95 interval and C50 to determine imprecision. We used the Roche Cobas clinical chemistry analyzer as a comparator, and we used leftover samples for imprecision studies. Studies on hemoglobin interference were done using plasma pool samples that had been spiked. Results: Our C50 concentration were 45 mg/dL, the C5-C95 30 mg/dL and 60 mg/dL, respectively. Two methods reveal an overall agreement of 89,2%. Conclusions Even low quantities of free hemoglobin caused a bias in ethanol values, according to the interference experiment. When it came to forensic samples, this bias was crucial. We demonstrated that the HemCheck can significantly improve the preanalytical quality, particularly in forensic specimens.